Evaluation of Intervention Measures on Controlling the Dissemination of Nontyphoidal Salmonella Disease in Mukuru Informal Settlement, Nairobi County, Kenya. - Kamwethya, Schola K. Peter; Joshua M. Mutiso; Samuel Kariuki (British Journal of Healthcare and Medical Research, 2023)
Nontyphoidal Salmonella is the most common bacterial pathogen causing gastrointestinal infection worldwide. Data is limited on the effectiveness of the intervention measures put in place to help control the dissemination of nontyphoidal Salmonella disease on Mukuru informal settlement in Nairobi County, Kenya. The aim of the study was to determine the effectiveness of the intervention measures put in place to prevent and control the dissemination of nontyphoidal Salmonella disease in Mukuru informal settlement in Nairobi County, Kenya. A cross-sectional study was conducted in patients aged 0-5 years. Nontyphoidal Salmonella (NTS) bacteria was cultured from blood and stool collected from the recruited children who reported at three health facilities with symptoms of diarrhea, fever or vomiting and antimicrobial susceptibility testing of the recovered NTS isolates from the stool and blood samples was performed. A questionnaire was administered to obtain relevant demographic, socio-economic and healthcare utilization information. Fisher’s test was conducted to determine the difference in the susceptibility patterns between the isolated NTS. Out of 191 collected samples, 3 were found to be positive for Salmonella Typhimurium and Salmonella Enteritidis. Both S. Typhimurium and S. Enteritidis isolates were resistant to gentamycin. Salmonella Typhimurium was found also to be resistant to tetracycline drug. Significant differences existed between some of the drugs susceptibility patterns (p= 0.0048). There are still AMR strains circulating in Mukuru informal settlement. There is still need for the Kenyan government to strengthen knowledge and understanding of AMR through supporting surveillance and research.